Cognitive Functions, Depressive and Anxiety Symptoms After One Year of CPAP Treatment in Obstructive Sleep Apnea - Vanek, Jakub; Prasko, Jan; Genzor, Samuel; Belohradova, Kamila; Visnovsky, Jozef; Mizera, Jan; Bocek, Jonas; Sova, Milan; Ociskova, Marie (Psychology research and behavior management, 2023)
OBJECTIVE: The study worked with depressive symptoms, anxiety score and cognitive functions in obstructive sleep apnea (OSA) patients treated with CPAP. METHODS: Eighty-one subjects with OSA and without psychiatric comorbidity were treated with CPAP for one year and completed the following scales and cognitive tests: Trail Making Test, Verbal Fluency Test, d2 Test, Beck Depression Inventory-II and Beck Anxiety Inventory. MINI ruled out psychiatric disorder. At the two months check-up, subjects were re-evaluated for depressive and anxiety symptoms, and after one year of CPAP treatment, subjects repeated cognitive tests and scales. Data about therapy adherence and effectiveness were obtained from the patient's CPAP machines. RESULTS: The study was completed by 59 CPAP adherent patients and eight non-adherent patients. CPAP therapy effectiveness was verified in all patients by decreasing the apnea-hypopnoea index below 5 and/or 10% of baseline values. The adherent patients significantly improved depressive and anxiety symptoms. There was also an improvement in overall performance in the attention test; however, performance in many individual items did not change. The adherent patients also improved verbal fluency and in the Part B of the Trail making test. The non-adherent group significantly increased the number of mistakes made in the d2 test; other results were non-significant. CONCLUSION: According to our results, OSA patients' mood, anxiety and certain cognitive domains improved during the one-year therapy with CPAP. TRIAL REGISTRATION NUMBER: NCT03866161.
Keywords: CPAP treatment; Verbal Fluency Test; obstructive sleep apnoea; treatment efficacy; Trail Making Test; depression; cognitive functions